Recent Advances in Fibrous Materials for Hydroelectricity Generation - Can Ge; Duo Xu; Xiao Feng; Xing Yang; Zheheng Song; Yuhang Song; Jingyu Chen; Yingcun Liu; Chong Gao; Yong Du; Zhe Sun; Weilin Xu; et al. (Nano-Micro Letters)
Highlights Fundamental principles and characteristics of fibrous materials-based hydroelectricity generation (FHG) are thoroughly reviewed. Fabrication strategies and advanced functions of FHG are discussed and summarized in detail. Challenges and perspectives of the next-generation development of FHG are discussed.